Nilai-Nilai Pendidikan Akhlak Dalam Film Iqro: Petualangan Meraih Bintang - Anissa Fitry; Rengga Satria (An-Nuha, 2022)
This research is motivated by the decline of morality in adolescents. This study aims to analyze the values ​​of moral education in the film Iqro: Petualangan Meraih Bintang. The benefits of this research are: 1) To increase knowledge about the value of moral education in the film Iqro: Petualangan Meraih Bintang; 2) As a source of information for educators and parents to know the value of moral education in the film Iqro: Petualangan Meraih Bintang; 3) As a reference for educators and parents in selecting and presenting educational programs for adolescents. This research is a literature study with the type of research specification using a content analysis approach. The results of the study show that the values ​​of moral education in the film Iqro: Petualangan Meraih Bintang are five, namely: 1) Morals to Allah, namely gratitude, patience and trust; 2) Morals to the Messenger of Allah, namely following the instructions of the Apostle; 3) Morals to oneself, namely persistent in learning the Qur'an, humble, and forgiving; 4) Morals to fellow human beings, namely helping, loving each other, giving gifts, giving advice to, and respecting both parents; 5) Morals to the universe, namely learning to study the universe, utilizing nature and its contents, and creating nature.